State, conflict, and democracy in Africa - edited by Richard Joseph (Boulder L. Rienner, 1999)
This volume explores important dimensions of state formation and erosion, social conflict and the gains and setbacks in democratization in contemporary Africa. The results of nearly a decade of research, reflection and collegial interaction, the collection delineates the dominant patterns of political restructuring since the upheavals of the early 1990s.
Includes bibliographical references (p. 471-510) and index.
Keywords: Democracy--Africa.